Influence of tree cover on herbaceous layer development and carbon and water fluxes in a Portuguese cork-oak woodland - Dubbert, Maren; Mosena, Alexander; Piayda, Arndt; Cuntz, Matthias; Correia, Alexandra Cristina; Pereira, João Santos; Werner, Christiane (Acta Oecologica, 2014)
Facilitation and competition between different vegetation layers may have a large impact on small-scale vegetation development. We propose that this should not only influence overall herbaceous layer yield but also species distribution and understory longevity, and hence the ecosystems carbon uptake capacity especially during spring. We analyzed the effects of trees on microclimate and soil properties (water and nitrate content) as well as the development of an herbaceous community layer regarding species composition, aboveground biomass and net water and carbon fluxes in a cork-oak woodland in Portugal, between April and November 2011. The presence of trees caused a significant reduction in photosynthetic active radiation of 35molm−2d−1 and in soil temperature of 5°C from April to October. At the same time differences in species composition between experimental plots located in open areas and directly below trees could be observed: species composition and abundance of functional groups became increasingly different between locations from mid April onwards. During late spring drought adapted native forbs had significantly higher cover and biomass in the open area while cover and biomass of grasses and nitrogen fixing forbs was highest under the trees. Further, evapotranspiration and net carbon exchange decreased significantly stronger under the tree crowns compared to the open during late spring and the die back of herbaceous plants occurred earlier and faster under trees. This was most likely caused by interspecific competition for water between trees and herbaceous plants, despite the more favorable microclimate conditions under the trees during the onset of summer drought.
Keywords: carbon fluxes; competition; Facilitation; Mediterranean; Plant interactions; Understory; water fluxes

Impact of wildfire return interval on the ectomycorrhizal resistant propagules communities of a Mediterranean open forest. - Buscardo, Erika; Rodríguez-Echeverría, Susana; Martín, María P.; De Angelis, Paolo; Pereira, João Santos; Freitas, Helena (Fungal biology, 2010)
Ectomycorrhizal (ECM) fungi, in particular their spores and other resistant propagules, play an important role in secondary succession processes that facilitate regeneration after disturbance events. In this study, the effects of high and low wildfire frequencies (respectively short and long fire return intervals) on the resistant propagules communities (RPCs) of a Mediterranean open pine forest were compared. Soil samples were collected in four mountain sites with different fire return intervals and used to test ectomycorrhiza development in two hosts, Pinus pinaster and Quercus suber. RPCs were characterized by direct sequencing of fungal internal transcribed spacer (ITS) regions from individual ECM root tips. Eighteen ECM species were detected in the bioassay. The most frequently found fungi were Cenococcum geophilum, Inocybe jacobi, Thelephora terrestris, Tomentella ellisii on both hosts and Rhizopogon luteolus and R. roseolus on maritime pine. A short fire return interval reduced the species richness of the ECM community found on Q. suber, promoted species like R. roseolus and reduced the abundance of other species (e.g. R. luteolus). The abundance of I. jacobi was positively affected by long fire return interval, but decreased significantly with recurrent fires. These results indicate that changes in fire frequency can alter the structure, composition and diversity of ECM communities, which could compromise the resilience of the ecosystem in highly disturbed areas.
The following values have no corresponding Zotero field: accession-num: 20943174
Keywords: Ectomycorrhizal resistant propagules community; Fire return interval; Mediterranean ecosystem; Pinus pinaster (maritime pine); Quercus suber (cork oak); succession

Hydraulic Lift in Cork Oak Trees in a Savannah-Type Mediterranean Ecosystem and its Contribution to the Local Water Balance - Kurz-Besson, Cathy; Otieno, Dennis; Lobo do Vale, Raquel; Siegwolf, Rolf; Schmidt, Markus; Herd, Alastair; Nogueira, Carla; David, Teresa Soares; David, Jorge Soares; Tenhunen, John; Pereira, João Santos; Chaves, Manuela (Plant and Soil, 2006)
The aim of this study was to identify the sources and depth of water uptake by 15-years old Quercus suber L. trees in southern Portugal under a Mediterranean climate, measuring d 18 O and dD in the soil–plantatmosphere continuum. Evidence for hydraulic lift was substantiated by the daily ﬂuctuations observed in Ys at 0.4 and 1 m depth and supported by similar d 18 O values found in tree xylem sap, soil water in the rhizosphere and groundwater. From 0.25 m down to a depth of 1 m, dD trends diﬀered according to vegetation type, showing a more depleted value in soil water collected under the evergreen trees ()47&) than under dead grasses ()35&). The hypothesis of a fractionation process occurring in the soil due to diﬀusion of water vapour in the dry soil is proposed to explain the more depleted soil dD signature observed under trees. Hydraulically lifted water was estimated to account for 17–81% of the water used during the following day by tree transpiration at the peak of the drought season, i.e., 0.1–14 L tree )1 day )1 . Signiﬁ- cant relationships found between xylem sap isotopic composition and leaf water potential in early September emphasized the positive impact of the redistribution of groundwater in the rhizosphere on tree water status.
Keywords: d 18 o; hydraulic lift; Quercus suber; root biomass; soil dd fractionation; soil water potential

Ensaios de proveniência de sobreiro (Quercus suber)-resultados aos cinco anos - Almeida, Maria Helena; Lourenço, Maria João; Nunes, A. M.; Sampaio, Teresa; VARELA, M. C.; Chambel, M. R.; Faria, C.; Pereira, João Santos (Congresso Florestal Nacional, 5º, Viseu, 2005, 2005)
A adaptabilidade do sobreiro às condições ambientais está pouco estudada e o uso de recursos genéticos inapropriados é uma das causas do insucesso de reflorestação tanto no curto como no longo prazo. Os resultados do esforço de florestação com sobreiro têm sido muito díspares, com valores médios de sobrevivência de 50% que oscilam entre o insucesso total e uma sobrevivência que, em alguns casos, atinge os 100%. A eventual alteração climática acentua a necessidade da utilização de material de reprodução adaptado, como meio de promover a sustentabilidade do montado e das florestas de sobreiro. A caracterização dos recursos genéticos desta espécie poderá contribuir também para a viabilidade económica e ambiental deste sistema ao identificar as populações mais adaptadas e os indivíduos produtores de melhor cortiça. A rede de ensaios de proveniência de sobreiro instalados em 1998, no âmbito da acção concertada “FAIR 1CT 95 0202”, onde estão representadas 35 populações cobrindo toda a sua área de distribuição natural são um excelente instrumento para a avaliação da adaptabilidade. Ainda que as respostas ao nível da qualidade da cortiça só possam ser obtidas tardiamente, o acompanhamento de parâmetros adaptativos ao longo do crescimento das árvores é importante e poderá fornecer informação relevante para a compreensão do funcionamento do sistema. Nesta comunicação apresentam-se os resultados obtidos, 5 anos após a instalação, nos ensaios de proveniência estabelecidos na Mata Nacional das Virtudes e no Monte da Fava relativamente a características adaptativas tais como: a sobrevivência, a eficiência do uso da água, o abrolhamento dos gomos foliares e o crescimento. Ao nível da sobrevivência as populações de origem francesa revelaram-se as menos adaptadas em ambos os locais. Quanto à altura, as 35 populações apresentaram crescimentos significativamente diferentes entre si nos dois ensaios, tendo as populações marroquinas registado os valores mais elevados. Relativamente ao abrolhamento dos gomos foliares observou-se um comportamento semelhante em termos das populações mais tardias e mais temporãs em ambos os ensaios. Geograficamente as primeiras localizam-se numa área mais ocidental da zona de distribuição natural da espécie enquanto que populações mais temporãs, com comportamento significativamente diferente das anteriores são originárias da região mais oriental.
The following values have no corresponding Zotero field: periodical: Congresso Florestal Nacional, 5º, Viseu, 2005
Keywords: adaptabilidade; proveniência; Quercus suber; sobreiro; variabilidade genética

Ensaios de proveniência de sobreiro (Quercus suber)-resultados aos cinco anos - Almeida, Maria Helena; Lourenço, Maria João; Nunes, A M; Sampaio, Teresa; Varela, M C; Chambel, M R; Faria, C; Pereira, João Santos (Congresso Florestal Nacional, 5º, Viseu, 2005, 2005)
A adaptabilidade do sobreiro às condições ambientais está pouco estudada e o uso de recursos genéticos inapropriados é uma das causas do insucesso de reflorestação tanto no curto como no longo prazo. Os resultados do esforço de florestação com sobreiro têm sido muito díspares, com valores médios de sobrevivência de 50% que oscilam entre o insucesso total e uma sobrevivência que, em alguns casos, atinge os 100%. A eventual alteração climática acentua a necessidade da utilização de material de reprodução adaptado, como meio de promover a sustentabilidade do montado e das florestas de sobreiro. A caracterização dos recursos genéticos desta espécie poderá contribuir também para a viabilidade económica e ambiental deste sistema ao identificar as populações mais adaptadas e os indivíduos produtores de melhor cortiça. A rede de ensaios de proveniência de sobreiro instalados em 1998, no âmbito da acção concertada “FAIR 1CT 95 0202”, onde estão representadas 35 populações cobrindo toda a sua área de distribuição natural são um excelente instrumento para a avaliação da adaptabilidade. Ainda que as respostas ao nível da qualidade da cortiça só possam ser obtidas tardiamente, o acompanhamento de parâmetros adaptativos ao longo do crescimento das árvores é importante e poderá fornecer informação relevante para a compreensão do funcionamento do sistema. Nesta comunicação apresentam-se os resultados obtidos, 5 anos após a instalação, nos ensaios de proveniência estabelecidos na Mata Nacional das Virtudes e no Monte da Fava relativamente a características adaptativas tais como: a sobrevivência, a eficiência do uso da água, o abrolhamento dos gomos foliares e o crescimento. Ao nível da sobrevivência as populações de origem francesa revelaram-se as menos adaptadas em ambos os locais. Quanto à altura, as 35 populações apresentaram crescimentos significativamente diferentes entre si nos dois ensaios, tendo as populações marroquinas registado os valores mais elevados. Relativamente ao abrolhamento dos gomos foliares observou-se um comportamento semelhante em termos das populações mais tardias e mais temporãs em ambos os ensaios. Geograficamente as primeiras localizam-se numa área mais ocidental da zona de distribuição natural da espécie enquanto que populações mais temporãs, com comportamento significativamente diferente das anteriores são originárias da região mais oriental.
Keywords: adaptabilidade; proveniência; Quercus suber; sobreiro; variabilidade genética

Pan-European δ13C values of air and organic matter from forest ecosystems - Hemming, Deborah; Yakir, Dan; Ambus, Per; Aurela, Mika; Besson, Cathy; Black, Kevin; Buchmann, Nina; Burlett, Regis; CESCATTI, ALESSANDRO; Clement, Robert; Gross, Patrick; Granier, André; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ13C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ13C values derived from large-scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem-scale δ13C values. In this framework, we also tested the potential of δ13C in canopy air and plant organic matter to record regional-scale ecophysiological patterns. Our network estimates for the mean δ13C of ecosystem respired CO2 and the related ‘discrimination’ of ecosystem respiration, δer and Δer, respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ13C values derived from regional-scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional-scale atmospheric sampling programs generally capture ecosystem δ13C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δer. From west to east, across the network, there was a general enrichment in 13C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δer values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature (Ta), but not significantly with monthly average precipitation (Pm). In contrast, in 2002 (a much wetter peak season), δer was significantly related with Ta, but not significantly with VPD and RH. The important role of plant physiological processes on δer in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time-lag analyses of δer vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δer and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δer signal during this season. Organic matter δ13C results showed progressive 13C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ13C values of organic matter of any of the plant components did not well represent short-term δer values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.
Keywords: carboeuroflux; CO2 fluxes; ecosystem carbon budget; ecosystem respiration; isotopic discrimination; Stable isotopes; δ13C

Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C.; Aillardc, Pascale M.; Cartazzad, Andrea S.; Rugnolid, Enrico B.; Havesa, Maria Manuela C.; Ereiraa, João Santos P. (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation

Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C; Aillardc, Pascale M; Cartazzad, Andrea S; Rugnolid, Enrico B; Havesa, Maria Manuela C; Ereiraa, João Santos P (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation

Efeito da Idade e da Fertilização na Qualidade das Plantas do Sobreiro (Quercus - Merouani, Hachemi; Costa, Filipe; Sampaio, Teresa; Lourenço, Maria João; Pereira, João Santos; Almeida, Maria Helena (Congresso Florestal Nacional, 5º, Viseu, 2005, 2003)
A plantação tem sido uma técnica muito utilizada em projectos de reflorestação do montado de sobro, uma vez que a sementeira é limitada temporalmente pelo facto de não se dominar a conservação a longo prazo das glandes (sementes recalcitrantes). Consequentemente, a produção das plantas provém exclusivamente de sementes frescas (Novembro - Janeiro) condicionando a sua idade no momento da plantação (10-14 meses). A idade da planta influencia o seu potencial de crescimento após a plantação, estando regulamentada por legislação (DecretoLei nº 205/2000, de 12 de Setembro). A aplicação de fertilizantes tem sido sugerida como uma técnica de produção em viveiro destinada a melhorar a qualidade da planta. No âmbito de diversos projectos (CREOAK-QLK5-CT-2002-01594; POCTI/41359/AGG/2001), temos vindo a aprofundar o conhecimento sobre a qualidade das plantas do sobreiro. Produziram-se em viveiro, plantas de idade diferente provenientes de sementes frescas e conservadas (3 e 6 meses), obtendo-se respectivamente plantas de 9, 7 e 5 meses. Nas plantas de 7 meses, foi aplicado um tratamento de fertilização (50 ml da solução NPK, 12-2-12) e de micorrização (Pisolithus tinctorius). Foram avaliados diferentes parâmetros morfológicos e fisiológicos durante a fase de crescimento da planta em viveiro, assim como o potencial de crescimento das raízes no momento de plantação. Os resultados apresentados centram-se no efeito de ambos os factores (idade à plantação e fertilização) na qualidade das plantas.
Keywords: Conservação de glandes; idade da planta; Material Florestal de Reprodução; Q. suber; Qualidade

Efeito da Idade e da Fertilização na Qualidade das Plantas do Sobreiro (Quercus - Merouani, Hachemi; Costa, Filipe; Sampaio, Teresa; Lourenço, Maria João; Pereira, João Santos; Almeida, Maria Helena (Congresso Florestal Nacional, 5º, Viseu, 2005, 2003)
A plantação tem sido uma técnica muito utilizada em projectos de reflorestação do montado de sobro, uma vez que a sementeira é limitada temporalmente pelo facto de não se dominar a conservação a longo prazo das glandes (sementes recalcitrantes). Consequentemente, a produção das plantas provém exclusivamente de sementes frescas (Novembro - Janeiro) condicionando a sua idade no momento da plantação (10-14 meses). A idade da planta influencia o seu potencial de crescimento após a plantação, estando regulamentada por legislação (DecretoLei nº 205/2000, de 12 de Setembro). A aplicação de fertilizantes tem sido sugerida como uma técnica de produção em viveiro destinada a melhorar a qualidade da planta. No âmbito de diversos projectos (CREOAK-QLK5-CT-2002-01594; POCTI/41359/AGG/2001), temos vindo a aprofundar o conhecimento sobre a qualidade das plantas do sobreiro. Produziram-se em viveiro, plantas de idade diferente provenientes de sementes frescas e conservadas (3 e 6 meses), obtendo-se respectivamente plantas de 9, 7 e 5 meses. Nas plantas de 7 meses, foi aplicado um tratamento de fertilização (50 ml da solução NPK, 12-2-12) e de micorrização (Pisolithus tinctorius). Foram avaliados diferentes parâmetros morfológicos e fisiológicos durante a fase de crescimento da planta em viveiro, assim como o potencial de crescimento das raízes no momento de plantação. Os resultados apresentados centram-se no efeito de ambos os factores (idade à plantação e fertilização) na qualidade das plantas.
The following values have no corresponding Zotero field: periodical: Congresso Florestal Nacional, 5º, Viseu, 2005
Keywords: Conservação de glandes; idade da planta; Material Florestal de Reprodução; Q. suber; Qualidade

Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow

Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow